The Ability of Company Performance and Accrual Components to Predict Future Cash Flows - Diah Saraswati; Agustin Ekadjaja (Manunggal Halim Jaya, 2026)
Financial information is essential for stakeholders as a basis for making economic decisions. Cash flow is a crucial indicator that enables stakeholders to evaluate a company's ability to sustain future operational activities. This study aims to examine the effects of net income, changes in accounts receivable, and changes in accounts payable on future cash flows. This study employs a quantitative research approach using a purposive sampling method based on a population of publicly listed companies in the Consumer Non-Cyclicals sector. The data are analyzed using panel data regression with the assistance of the E-Views application. The results indicate that net income and changes in accounts receivable have a significant effect on future cash flows, whereas changes in accounts payable do not have a significant effect. Simultaneously, the three variables significantly influence future cash flows. These findings confirm that future cash flows are primarily influenced by company performance and accrued income rather than accrued expenses.